IMPLEMENTASI LOAD BALANCING MENGGUNAKAN METODE PCC (PER CONNECTION CLASIFIER) DI UNIVERSITAS KRISNADWIPAYANA - Imam Sujarwo; Desmulyati Desmulyati; Imam Budiawan (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
On the internet connection with 2 service ISP (Internet Service Provider) to consider the possibility of interruption on the internet connection. PCC (Per Connection Clasifier) is a method of load balancing in the merge 2 ISP service. Internet network connection is needed by a company or agency that performs each job with depend internet network connection. It is therefore necessary internet network are always standby when the failure occurs the internet connection. At this writing performed a system. First test done with 1 ISP service. Testing both with the use of PCC in the normal state and with the use of PCC occurs when lost connection on one of the links. By using 2 ISP services can be separated between local bandwidth and internasioan done on the second test. On testing the second can be proved that by using the 2 service ISP with load balancing PCC and much better against the service connection network the internet because there is a system that is always on standby when it happened lost connection on one of the links. With system blocks the IP automatically can protect the server mikrotik from attack heacker.